A toxicological evaluation of lithium orotate - Murbach, Timothy S.; Glávits, Róbert; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics (Regulatory toxicology and pharmacology, 2021)
Lithium orotate, the salt of lithium and orotic acid, has been marketed for decades as a supplemental source of lithium with few recorded adverse events. Nonetheless, there have been some concerns in the scientific literature regarding orotic acid, and pharmaceutical lithium salts are known to have a narrow therapeutic window, albeit, at lithium equivalent therapeutic doses 5.5–67 times greater than typically recommended for supplemental lithium orotate. To our knowledge, the potential toxicity of lithium orotate has not been investigated in preclinical studies; thus, we conducted a battery of genetic toxicity tests and an oral repeated-dose toxicity test in order to further explore its safety. Lithium orotate was not mutagenic or clastogenic in bacterial reverse mutation and in vitro mammalian chromosomal aberration tests, respectively, and did not exhibit in vivo genotoxicity in a micronucleus test in mice. In a 28-day, repeated-dose oral toxicity study, rats were administered 0, 100, 200, or 400 mg/kg body weight/day of lithium orotate by gavage. No toxicity or target organs were identified; therefore, a no observed adverse effect level was determined as 400 mg/kg body weight/day. These results are supportive of the lack of a postmarket safety signal from several decades of human consumption. •This is the first preclinical toxicologic evaluation of lithium orotate.•No in vitro or in vivo genotoxic effects were observed in a standard test battery.•No treatment related adverse effects were observed in Wistar rats.•No target organs were identified in Wistar rats.•The NOAEL was 400 mg/kg bw/day, the highest dose tested.